Working towards peace through yoga : Qualitative assessment of yoga program in a social housing complex in Santa Marta, Colombia (2017)
The goal of the study was to evaluate perceived mental and physical health benefits of yoga for people living in Ciudad Equidad, a social housing complex in Santa Marta, Colombia. The participants of the study voluntarily enrolled to complete two yoga sessions per week, each lasting 1.5 hours, during a three-month period. Additionally, they participated in baseline and end-program focus groups and post-intervention semistructured interviews. These qualitative assessments were intended to measure perceived changes in aggressiveness, coping strategies, emotional intelligence and stress among others. Data analysis revealed that yoga participants perceived significant changes over time in relation to when they began the intervention in all measures included (aggressiveness, emotional intelligence, coping strategies and stress). These preliminary results suggest that implementation of yoga is a feasible and effective alternative to improve co-existence and manage violence among neighbors in Ciudad Equidad